Estudo da reciclagem de cinza volante para produção de agregado sintético utilizando reator de leito fixo - PEREIRA, Luiz Felipe Silva (Universidade Federal do Pará, 2017)
The use of such industrial waste boiler fly ash for recycling and reuse, has intensified in recent years much for its physico-chemical characteristics that may result after the processing, in a material with good mechanical strength and can be designed for use in several areas such as construction. In this paper we obtain synthetic aggregates, after sintering process in a fixed bed reactor. For the production of aggregates pellet sewed up mixer from a mixing wheel boiler ash, clay and charcoal. After the process of ceramic sintering were measured material properties such that: porosity, density and water absorption. For the characterization of phases and mineralogical structures of the sintered material, we used the techniques of X-ray diffraction and scanning electron microscopy. Thus the contribution of this work is aimed at reducing environmental impacts, due to the possibility that the material produced has to replace natural aggregates.